A modified sulphoaluminate cement protective material containing rare earth and preparation method thereof
By adding cement active modifiers to sulfaluminate cement to activate cement particles, the problems of unfriendly and insufficient strength of existing waterproof materials are solved, and high strength, high viscosity and good waterproof functions are achieved.
Patent Information
- Application Number
- CN202510041433.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-10
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-01-10
AI Technical Summary
Most of the existing waterproof materials are organic polymer materials, which have problems such as toxic gas release during production and construction, unfriendly environment, and easy degradation and failure under wind and sun exposure. The cement-based permeable crystalline waterproof materials have low strength and limited application range.
Using modified sulfa aluminate cement protective material containing rare earth, cement particles are activated and their adhesion to other materials are enhanced by adding cement active modifiers, including active agents modified by passivation layer and decomposition solution.
It realizes high strength, high viscosity and good waterproof functions, avoids the problems of decreasing strength and deteriorating crack resistance caused by excessive viscosity of cement protective materials during construction, and is also environmentally friendly.
Smart Images

Figure CN119490341B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of cement-based protection, and relates to a modified sulphoaluminate cement protective material containing rare earth and a preparation method thereof. Background Art
[0002] Waterproof materials have gone through many years and have a wide variety of varieties, but they are mainly based on high-molecular organic materials, such as asphalt waterproof materials, acrylic waterproof materials, polyurethane waterproof materials, rubber plastic waterproof materials, etc. These materials are basically secondary production after petroleum refining. Toxic gases are released during the production process and during construction. Most of them use open flames during construction, which is not friendly to the environment and humans. Because they are organic materials, they will degrade and fail over a long period of time in the wind and sun environment, which can easily cause water leakage in buildings. There is also a cement-based permeable crystalline waterproof material, which requires frequent maintenance and has low strength, so its application range is not wide. Therefore, there is currently a lack of a high-strength, high-viscosity and environmentally friendly anti-seepage and waterproof protective material. Summary of the invention
[0003] The purpose of the present invention is to provide a rare earth-containing modified sulphoaluminate cement protective material and a preparation method thereof, so as to solve the problem of the current lack of a high-strength, high-viscosity and environmentally friendly anti-seepage and waterproof protective material.
[0004] The technical solution adopted by the present invention is as follows:
[0005] A rare earth-containing modified sulphoaluminate cement protective material, comprising the following components in parts by weight: 60 parts of composite sulphoaluminate cement, 25-26 parts of admixture, 2-3 parts of cement active modifier, 2-3 parts of auxiliary agent, and a water-solid ratio of 0.4;
[0006] The cement active modifier comprises component A and component B;
[0007] The component A is an active agent that is surface-inertly modified by a passivation layer, wherein the passivation layer comprises ethylene-tetrafluoroethylene copolymer, silk fibroin modified fiber, silane coupling agent, and glycidyl methacrylate graft-modified soybean protein adhesive;
[0008] The mass ratio of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber is 4:3, the addition amount of glycidyl methacrylate grafted modified soybean protein adhesive is 10% of the sum of the mass of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber, and the addition amount of silane coupling agent is 3% of the sum of the mass of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber;
[0009] The component B is a decomposition liquid of the passivation layer in the component A, and the component B comprises papain and neutral protease.
[0010] Sulphoaluminate cement has excellent properties such as early strength, high strength, impermeability, frost resistance, corrosion resistance and low alkalinity, and is generally used in winter construction, hydraulic engineering, repair engineering and other special projects. Therefore, the present invention uses sulphoaluminate cement as the main material, and on this basis, the present invention adds a cement active modifier to improve the activity of cement particles, thereby strengthening the bonding force between cement particles and other materials, and finally obtains a protective material with both extremely strong bonding and good waterproof function.
[0011] The cement active modifier in the present invention comprises component A and component B. The present invention firstly performs passivation modification on the surface of the active agent to avoid the active agent excessively enhancing the activity of cement particles in the early stage, making the bonding force of cement particles too strong and generating excessive cohesion, which in turn leads to the decrease of strength of cement protective materials and the deterioration of crack resistance. The component B in the present invention is used to destroy the passivation layer of component A, so that the active agent in component A contacts with the surface of cement particles, stimulates the activity of the surface of cement particles, and strengthens the bonding force between cement particles and other materials.
[0012] The main components of component A include inert ethylene-tetrafluoroethylene copolymer. The chemical properties of ethylene-tetrafluoroethylene copolymer are very stable and it is not easy to react with other substances. Therefore, the present invention adopts ethylene-tetrafluoroethylene copolymer as one of the main materials to isolate the active agent from contact with cement particles, thereby playing a passivation role of the active agent; on the basis of ethylene-tetrafluoroethylene copolymer, the present invention adds silk fibroin modified fiber, silane coupling agent, and methacrylic acid glycidyl grafted modified soybean protein adhesive. Under the action of silane coupling agent and methacrylic acid glycidyl grafted modified soybean protein adhesive, the silk fibroin modified fiber and ethylene-tetrafluoroethylene copolymer are bonded to each other. The ethylene copolymer is blended and bonded together; the silk fibroin modified fiber and the soybean protein adhesive grafted with glycidyl methacrylate contain protein, which is hydrolyzed and the structure is destroyed under the action of protein enzymes (papain, neutral protease); therefore, the present invention utilizes enzymatic hydrolysis technology, and the enzyme in component B hydrolyzes the silk fibroin modified fiber and the soybean protein adhesive grafted with glycidyl methacrylate in component A, and after the structure of the silk fibroin modified fiber and the soybean protein adhesive grafted with glycidyl methacrylate is destroyed, the passivation layer formed by the blending of the silk fibroin modified fiber and the ethylene-tetrafluoroethylene copolymer is The structure is also destroyed, forming a large number of fragments and other substances, which fill the gaps in the cement slurry. Since the ethylene-tetrafluoroethylene copolymer has stable chemical properties and certain waterproof properties, it helps to enhance the waterproof property of the cement after mixing with cement. The passivation layer formed by the blending of silk fibroin modified fiber and ethylene-tetrafluoroethylene copolymer is gradually broken under the action of enzymatic hydrolysis, and the active agent inside is released and contacts with cement particles to activate the cement particles. Since enzymatic hydrolysis is a process with a reaction time, the reaction time of the present invention is about 2-3 hours. During this process, the active agent will be continuously released to contact the cement particles. The active agent is directly in contact with the cement particles during mixing. In the prior art, the active agent is directly in contact with the cement particles during mixing, and the bonding force of the cement particles reaches a maximum within a very short time (a few minutes), resulting in excessive cohesion inside the cement slurry. The present invention solves the above problems, and the prepared protective material has both extremely strong adhesion and good waterproof function and mechanical strength.
[0013] Furthermore, the active agent in component A includes the following components in parts by weight: 5 parts of redispersible latex powder, 4 parts of lanthanum cerium oxide, 2 parts of starch ether, and 2 parts of low-viscosity cellulose ether.
[0014] The present invention uses lanthanum cerium oxide as one of the main materials to prepare an activating agent, which has an obvious activation effect on cement.
[0015] Furthermore, the admixture includes the following components in parts by weight: 12 parts of 200-mesh refined iron powder, 6 parts of 150-mesh magnetite, 3 parts of 1250-mesh microsilica powder, and 10 parts of fly ash.
[0016] The present invention is based on the close packing theory and preferably mixes fillers with multiple particle sizes with cement.
[0017] Furthermore, the additives include the following components: a water reducer and a defoamer, wherein the amount of the water reducer is 1-1.2% of the mass of the composite sulphoaluminate cement, and the amount of the defoamer is 0.4-0.5% of the mass of the composite sulphoaluminate cement; wherein the water reducer is a polycarboxylate water reducer and the defoamer is a silicone defoamer.
[0018] Polycarboxylic acid water reducers and silicone defoamers are both existing technologies.
[0019] Furthermore, the silk fibroin modified fiber is prepared by the following method: putting tussah silkworm cocoons into a sodium carbonate solution with a mass percentage of 0.5% at a bath ratio of 1:50, placing the solution in a constant temperature water bath and boiling for 30 minutes, then taking it out, putting the tussah silkworm cocoons into a sodium carbonate solution with a mass percentage of 0.5% at a bath ratio of 1:50 again, and boiling it in a water bath for 30 minutes, repeating the boiling for 3 times, taking out the boiled tussah silkworm cocoons, drying them in an oven at a temperature of 60°C to constant weight, using scissors to cut the tussah silkworm cocoons into pieces, putting them into a 9 mol / L ammonium thiocyanate solution at a bath ratio of 1:35, dissolving and filtering, and then dialysis filtering in circulating deionized water for 48 hours, and concentrating the silk fibroin solution obtained by dialysis filtration to a mass percentage of 6%;
[0020] According to the bath ratio of 1:20, the viscose fiber was put into a 6% silk fibroin solution by mass, and the solution was placed in a constant temperature water bath at a temperature of 55°C. Under the stirring action of an electric stirrer, the solution was taken out after grafting for 45 minutes, placed in an oven at a temperature of 60°C and dried to constant weight, and then repeatedly washed with deionized water. The washed silk fibroin modified viscose fiber was placed in an oven at a temperature of 60°C and dried to constant weight to obtain silk fibroin modified fiber.
[0021] Furthermore, the glycidyl methacrylate grafted modified soybean protein adhesive is prepared by the following method: adding soybean protein and urea solution into a reaction container, pre-treating in an oil bath at 50° C. for 30 minutes, adding ammonium persulfate and sodium bisulfite initiators into the reaction container, adding glycidyl methacrylate during the reaction for 10 minutes, heating to 70° C., continuing the reaction for 3 hours, and then stopping the reaction to obtain the glycidyl methacrylate grafted modified soybean protein adhesive;
[0022] Among them, the mass ratio of soy protein to glycidyl methacrylate is 4:3.4.
[0023] Furthermore, the composite sulphoaluminate cement comprises 42.5 sulphoaluminate cement and 42.5 silicate cement in a mass ratio of 3:1.
[0024] 42.5 sulphoaluminate cement hardens quickly and strengthens early, and has good water resistance and impermeability; 42.5 silicate cement has higher strength and higher durability; therefore, the present invention compounds the two, and the obtained composite material not only hardens quickly and strengthens early, has good water resistance and impermeability, but also has higher strength.
[0025] Furthermore, the mass ratio of papain to neutral protease in component B is 0.5-0.75.
[0026] Furthermore, the added amount of component B is 0.5%-0.6% of the total mass of component A.
[0027] A method for preparing a modified sulphoaluminate cement protective material containing rare earth comprises the following steps:
[0028] S1. Prepare component A: select redispersible latex powder, lanthanum cerium oxide, starch ether, and low-viscosity cellulose ether as raw materials for the active agent, and compress and granulate the redispersible latex powder, lanthanum cerium oxide, starch ether, and low-viscosity cellulose ether in a dry granulator to obtain active agent particles for standby use;
[0029] Adding silk fibroin modified fiber, silane coupling agent, and glycidyl methacrylate grafted modified soybean protein adhesive into the melt of ethylene-tetrafluoroethylene copolymer, stirring at a constant temperature of 50° C. for 2-3 hours, to obtain a passivating agent;
[0030] The passivating agent is uniformly sprayed on the active agent particles, and after drying, the active agent with surface inertness modified by the passivating layer is obtained, wherein the active agent with surface inertness modified by the passivating layer is component A;
[0031] Preparation of component B: using papain and neutral protease as raw materials to prepare enzymatic hydrolysis solution, component B is used together with component A;
[0032] S2. According to the water-to-solid ratio of 0.4, the composite sulphoaluminate cement, admixture, component A, component B and additives are placed in a mixing tank containing water, stirred at a speed of 300 rpm for 3 minutes, allowed to stand for 1 minute for maturation, and stirred for another minute to obtain the sulphoaluminate cement protective material.
[0033] In summary, due to the adoption of the above technical solution, the beneficial effects of the present invention are:
[0034] 1. A rare earth-containing modified sulphoaluminate cement protective material uses sulphoaluminate cement as the main material. On this basis, the present invention adds a cement active modifier to enhance the activity of cement particles, thereby strengthening the bonding force between cement particles and other materials, and finally obtaining a protective material with both extremely strong adhesion and good waterproof function;
[0035] 2. The present invention compounds 42.5 sulphoaluminate cement with 42.5 silicate cement to obtain a composite material that not only has fast hardening and early strength, good water resistance and impermeability, but also has high strength;
[0036] 3. The present invention utilizes enzymatic hydrolysis technology. The passivation layer formed by blending the silk fibroin modified fiber and the ethylene-tetrafluoroethylene copolymer gradually breaks under the action of enzymatic hydrolysis, and the active agent inside is released and contacts with the cement particles to activate the cement particles, thereby avoiding the generation of a large cohesive force inside the cement slurry during the activation process, thereby causing the strength of the protective material to be reduced;
[0037] 4. After the structures of the silk fibroin modified fiber and the soybean protein adhesive grafted with glycidyl methacrylate are destroyed, the structure of the passivation layer formed by blending the silk fibroin modified fiber and the ethylene-tetrafluoroethylene copolymer is also destroyed, forming a large amount of fragments and other substances, which fill the gaps in the cement slurry. Since the ethylene-tetrafluoroethylene copolymer has stable chemical properties and certain waterproof properties, it can also help to enhance the waterproof properties of the cement after mixing with the cement. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the following briefly introduces the drawings required for use in the embodiments. It should be understood that the following drawings only illustrate certain embodiments of the present invention and should not be regarded as limiting the scope. For those skilled in the art, other related drawings can be obtained based on these drawings without creative work, among which:
[0039] Figure 1 This is a microscopic image of the passivation layer of component A of the present invention. DETAILED DESCRIPTION
[0040] In order to make the purpose, technical scheme and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the accompanying drawings and embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention, that is, the embodiments described are only part of the embodiments of the present invention, rather than all of the embodiments. The components of the embodiments of the present invention described and shown in the drawings herein can be arranged and designed in various different configurations.
[0041] Therefore, the following detailed description of the embodiments of the present invention provided in the accompanying drawings is not intended to limit the scope of the invention claimed for protection, but merely represents selected embodiments of the present invention. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without making creative work are within the scope of protection of the present invention.
[0042] It should be noted that relational terms such as "first" and "second" are used only to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of further restrictions, the elements defined by the sentence "comprise a ..." do not exclude the existence of other identical elements in the process, method, article or device including the elements.
[0043] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0044] Example 1
[0045] A modified sulphoaluminate cement protective material containing rare earth provided in a preferred embodiment of the present invention comprises the following components in parts by weight: 60 parts of composite sulphoaluminate cement, 25-26 parts of admixture, 2-3 parts of cement active modifier, 2-3 parts of auxiliary agent, and a water-solid ratio of 0.4;
[0046] The cement active modifier comprises component A and component B, and the added amount of component B is 0.5% of the total mass of component A.
[0047] The component A is an active agent that is surface-inertly modified by a passivation layer, wherein the passivation layer comprises ethylene-tetrafluoroethylene copolymer, silk fibroin modified fiber, silane coupling agent, and glycidyl methacrylate graft-modified soybean protein adhesive;
[0048] The mass ratio of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber is 4:3, the addition amount of glycidyl methacrylate grafted modified soybean protein adhesive is 10% of the sum of the mass of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber, and the addition amount of silane coupling agent is 3% of the sum of the mass of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber;
[0049] The component B is a decomposition liquid of the passivation layer in the component A. The component B comprises papain and neutral protease. The mass ratio of papain to neutral protease in the component B is 0.5.
[0050] The active agent in component A comprises the following components in parts by weight: 5 parts of redispersible latex powder, 4 parts of lanthanum cerium oxide, 2 parts of starch ether, and 2 parts of low-viscosity cellulose ether.
[0051] The admixture includes the following components in parts by weight: 12 parts of 200-mesh refined iron powder, 6 parts of 150-mesh magnetite, 3 parts of 1250-mesh microsilica powder, and 10 parts of fly ash.
[0052] The additives include the following components: a water reducer and a defoamer. The amount of the water reducer is 1-1.2% of the mass of the composite sulphoaluminate cement, and the amount of the defoamer is 0.4-0.5% of the mass of the composite sulphoaluminate cement. The water reducer is a polycarboxylate water reducer, and the defoamer is an organosilicon defoamer.
[0053] The silk fibroin modified fiber is prepared by the following method: putting tussah silkworm cocoons into a sodium carbonate solution with a mass percentage of 0.5% at a bath ratio of 1:50, placing the solution in a constant temperature water bath and boiling for 30 minutes, then taking it out, putting the tussah silkworm cocoons into a sodium carbonate solution with a mass percentage of 0.5% at a bath ratio of 1:50 again, and boiling it in a water bath for 30 minutes, repeating the boiling for 3 times, taking out the boiled tussah silkworm cocoons, drying them in an oven at a temperature of 60° C. to constant weight, cutting the tussah silkworm cocoons into pieces with scissors, putting them into a 9 mol / L ammonium thiocyanate solution at a bath ratio of 1:35, dissolving and filtering, and then dialysis filtering in circulating deionized water for 48 hours, and concentrating the silk fibroin solution obtained by dialysis filtering to a mass percentage of 6%;
[0054] According to the bath ratio of 1:20, the viscose fiber was put into a 6% silk fibroin solution by mass, and the solution was placed in a constant temperature water bath at a temperature of 55°C. Under the stirring action of an electric stirrer, the solution was taken out after grafting for 45 minutes, placed in an oven at a temperature of 60°C and dried to constant weight, and then repeatedly washed with deionized water. The washed silk fibroin modified viscose fiber was placed in an oven at a temperature of 60°C and dried to constant weight to obtain silk fibroin modified fiber.
[0055] The glycidyl methacrylate grafted modified soybean protein adhesive is prepared by the following method: adding soybean protein and urea solution into a reaction container, pre-treating in an oil bath at 50° C. for 30 minutes, adding ammonium persulfate and sodium bisulfite initiators into the reaction container, adding glycidyl methacrylate during the reaction for 10 minutes, heating to 70° C., continuing the reaction for 3 hours and then stopping the reaction to obtain the glycidyl methacrylate grafted modified soybean protein adhesive;
[0056] Among them, the mass ratio of soy protein to glycidyl methacrylate is 4:3.4.
[0057] The composite sulphoaluminate cement comprises 42.5 sulphoaluminate cement and 42.5 silicate cement in a mass ratio of 3:1.
[0058] A method for preparing a modified sulphoaluminate cement protective material containing rare earth comprises the following steps:
[0059] S1. Prepare component A: select redispersible latex powder, lanthanum cerium oxide, starch ether, and low-viscosity cellulose ether as raw materials for the active agent, and compress and granulate the redispersible latex powder, lanthanum cerium oxide, starch ether, and low-viscosity cellulose ether in a dry granulator to obtain active agent particles for standby use;
[0060] Adding silk fibroin modified fiber, silane coupling agent, and glycidyl methacrylate grafted modified soybean protein adhesive into the melt of ethylene-tetrafluoroethylene copolymer, stirring at a constant temperature of 50° C. for 2-3 hours, to obtain a passivating agent;
[0061] The passivating agent is uniformly sprayed on the active agent particles, and after drying, the active agent with surface inertness modified by the passivating layer is obtained, wherein the active agent with surface inertness modified by the passivating layer is component A;
[0062] Preparation of component B: using papain and neutral protease as raw materials to prepare enzymatic hydrolysis solution, component B is used together with component A;
[0063] S2. According to the water-to-solid ratio of 0.4, the composite sulphoaluminate cement, admixture, component A, component B and additives are placed in a mixing tank containing water, stirred at a speed of 300 rpm for 3 minutes, allowed to stand for 1 minute for maturation, and stirred for another minute to obtain the sulphoaluminate cement protective material.
[0064] Figure 1 It is a microscopic picture of the passivation layer of the present invention, such as Figure 1 As shown, there is an obvious fiber structure in the passivation layer formed by component A in the present invention, indicating that the silk fibroin modified fiber and the ethylene-tetrafluoroethylene copolymer are successfully blended.
[0065] In order to detect whether the enzymatic hydrolyzate in component B has a destructive effect on the passivation layer in component A, the present invention prepares a large-area passivation layer coating according to the formula of the passivation layer given in component A, and immerses the test piece attached with the coating in component B. After 15 minutes, cracks are observed in the passivation coating with the naked eye, indicating that component B of the present invention has a destructive effect on the passivation layer in component A.
[0066] Example 2
[0067] This embodiment is based on Embodiment 1. The difference from Embodiment 1 is that the cement active modifier in this embodiment includes component A and component B, and the addition amount of component B is 0.55% of the total mass of component A.
[0068] Example 3
[0069] This embodiment is based on Embodiment 1. The difference from Embodiment 1 is that the cement active modifier in this embodiment includes component A and component B, and the addition amount of component B is 0.6% of the total mass of component A.
[0070] Example 4
[0071] This example is based on Example 1, and is different from Example 1 in that the component B in this example includes papain and neutral protease, and the mass ratio of papain to neutral protease in the component B is 0.6.
[0072] Example 5
[0073] This example is based on Example 1, and is different from Example 1 in that the component B in this example includes papain and neutral protease, and the mass ratio of papain to neutral protease in the component B is 0.75.
[0074] Example 6
[0075] This example is based on Example 2, and is different from Example 2 in that the component B in this example includes papain and neutral protease, and the mass ratio of papain to neutral protease in the component B is 0.6.
[0076] Example 7
[0077] This example is based on Example 3, and is different from Example 3 in that the component B in this example includes papain and neutral protease, and the mass ratio of papain to neutral protease in the component B is 0.75.
[0078] Example 8
[0079] This example is based on Example 3, and is different from Example 3 in that the component B in this example includes papain and neutral protease, and the mass ratio of papain to neutral protease in the component B is 0.6.
[0080] Example 9
[0081] This example is based on Example 3, and is different from Example 3 in that the component B in this example includes papain and neutral protease, and the mass ratio of papain to neutral protease in the component B is 0.75.
[0082] Comparative Example 1
[0083] The comparative example provides a rare earth-containing modified sulphoaluminate cement protective material, comprising the following components in parts by weight: 60 parts of composite sulphoaluminate cement, 25-26 parts of admixture, 2-3 parts of cement active modifier, 2-3 parts of additive, and a water-solid ratio of 0.4;
[0084] The active agent in component A comprises the following components in parts by weight: 5 parts of redispersible latex powder, 4 parts of lanthanum cerium oxide, 2 parts of starch ether, and 2 parts of low-viscosity cellulose ether.
[0085] The admixture includes the following components in parts by weight: 12 parts of 200-mesh refined iron powder, 6 parts of 150-mesh magnetite, 3 parts of 1250-mesh microsilica powder, and 10 parts of fly ash.
[0086] The additives include the following components: a water reducer and a defoamer. The amount of the water reducer is 1-1.2% of the mass of the composite sulphoaluminate cement, and the amount of the defoamer is 0.4-0.5% of the mass of the composite sulphoaluminate cement. The water reducer is a polycarboxylate water reducer, and the defoamer is an organosilicon defoamer.
[0087] The difference between this comparative example and Example 1 is that the cement active modifier in this comparative example does not undergo passivation treatment on the active agent, and the active agent is directly mixed with other raw materials and then stirred to obtain the protective material.
[0088] Comparative Example 2
[0089] Based on Example 8, the component B in this comparative example includes papain and neutral protease, the mass ratio of papain to neutral protease in the component B is 0.6, the cement active modifier includes component A and component B, and the addition amount of the component B is 0.7% of the total mass of component A.
[0090] Comparative Example 3
[0091] Based on Example 1, the active agent in component A of this comparative example does not include redispersible latex powder.
[0092] Comparative Example 4
[0093] Based on Example 1, the active agent in component A of this comparative example does not include lanthanum cerium oxide.
[0094] Comparative Example 5
[0095] Based on Example 1, the active agent in component A of this comparative example does not include starch ether.
[0096] Comparative Example 6
[0097] Based on Example 1, the active agent in component A of this comparative example does not include the following components in parts by weight: low-viscosity cellulose ether.
[0098] Comparative Example 7
[0099] Based on Example 8, the water-to-solid ratio of this comparative example is 0.5.
[0100] Comparative Example 8
[0101] Based on Example 8, the water-to-solid ratio of this comparative example is 0.35.
[0102] Comparative Example 9
[0103] Based on Example 1, the passivation layer of component A in this comparative example does not include ethylene-tetrafluoroethylene copolymer.
[0104] Comparative Example 10
[0105] Based on Example 1, the passivation layer of component A in this comparative example does not include silk fibroin modified fibers.
[0106] Comparative Example 11
[0107] Based on Example 1, the passivation layer of component A in this comparative example does not include the soybean protein adhesive graft-modified with glycidyl methacrylate.
[0108] Comparative Example 12
[0109] Based on Example 1, the component B in this comparative example does not include papain.
[0110] Comparative Example 13
[0111] Based on Example 1, the component B in this comparative example does not include neutral protease.
[0112] Test Example 1
[0113] In this test example, the strength and bonding properties of the protective materials prepared in Examples 1-9 and Comparative Examples 1-13 were tested.
[0114] The strength of the protective materials prepared in Examples 1-9 and Comparative Examples 1-13 was measured with reference to the standard DL / T5126-2021 "Test Procedure for Polymer Modified Cement Mortar". The results are shown in Table 1.
[0115] Table 1 Strength test results of protective materials
[0116] 1d compressive strengthMpa 28d compressive strength Mpa 28d flexural strength Mpa 2h bonding strengthMpa Example 1 >35 >80 >10 2.5-3 Example 2 >35 >80 >10 2.5-3 Example 3 >35 >80 >10 2.5-3 Example 4 >35 >80 >10 2.5-3 Example 5 >35 >80 >10 2.5-3 Example 6 >35 >80 >10 2.5-3 Example 7 >35 >80 >10 2.5-3 Example 8 >35 >80 >10 >3 Example 9 >35 >80 >10 2.5-3 Comparative Example 1 >35 60-65 <10 3-3.5 Comparative Example 2 >35 72-74 >10 3.4-3.5 Comparative Example 3 >35 68-70 <10 1.86-2 Comparative Example 4 >35 73-74 <10 0.83-1.25 Comparative Example 5 >35 72-74 <10 1.78-1.89 Comparative Example 6 >35 74-75 <10 1.87-1.89 Comparative Example 7 <35 <60 >10 2-2.15 Comparative Example 8 >35 >80 <10 2.3-2.4 Comparative Example 9 >35 <80 <10 2.5-3 Comparative Example 10 <35 <50 <10 <1 Comparative Example 11 >35 >80 >10 <1 Comparative Example 12 >35 >80 >10 <1 Comparative Example 13 >35 >80 >10 <1
[0117] The compressive strength, flexural strength and bonding strength of the protective material prepared by the present invention are all good. Compared with comparative example 1, the bonding strength of the present invention after curing for 2 hours is not much different from that of comparative example 1, but the compressive strength of the present invention is significantly higher than that of comparative example 1.
[0118] Test Example 2
[0119] In this test example, the anti-seepage and waterproof performance of the protective materials prepared in Examples 1-9 and Comparative Examples 1-13 were tested.
[0120] The method for testing the waterproof performance is: after curing for 28 days, the test piece prepared by the protective material is immersed in water for 7 days to observe whether water seepage occurs on the surface of the test piece. The results are shown in Table 2. This method is simple and easy to use and can quickly determine the waterproof performance of the protective material.
[0121] Anti-seepage performance test: The protective material is prepared into a cylindrical or cubic specimen. The test surface size of the specimen is not less than 150 mm, and the other surface sizes are not less than 100 mm. The size of the test area is about 1 / 2 of the test surface size. After curing for 28 days, the penetration depth of the specimen is measured under the conditions of a water pressure of 0.5 MPa and a pressure holding time of 72 h. The results are shown in Table 2.
[0122] Table 2 Test results of protective materials
[0123] Waterproof Penetration Depth Example 1 No water seepage <0.5mm Example 2 No water seepage <0.5mm Example 3 No water seepage <0.5mm Example 4 No water seepage <0.5mm Example 5 No water seepage <0.5mm Example 6 No water seepage <0.5mm Example 7 No water seepage <0.5mm Example 8 No water seepage <0.5mm Example 9 No water seepage <0.5mm Comparative Example 1 Local water seepage 0.5-1mm Comparative Example 2 No water seepage <0.5mm Comparative Example 3 Local water seepage 0.5-1mm Comparative Example 4 Local water seepage 0.5-1mm Comparative Example 5 Local water seepage 0.5-1mm Comparative Example 6 Local water seepage 0.5-1mm Comparative Example 7 No water seepage <0.5mm Comparative Example 8 No water seepage <0.5mm Comparative Example 9 Local water seepage 0.5-1mm Comparative Example 10 Local water seepage 0.5-1mm Comparative Example 11 Local water seepage 0.5-1mm Comparative Example 12 Local water seepage 0.5-1mm Comparative Example 13 Local water seepage 0.5-1mm
[0124] Compared with the above comparative example, the waterproof and anti-seepage performance of the present invention is good.
[0125] The above description is only a preferred embodiment of the present invention and is not intended to limit the scope of protection of the present invention. Any modifications, equivalent substitutions and improvements made by any technician familiar with the field within the spirit and principle of the present invention should be included in the scope of protection of the present invention.
Claims
1. A rare earth-containing modified sulphoaluminate cement protective material, characterized in that: The invention comprises the following components in parts by weight: 60 parts of composite sulphoaluminate cement, 25-26 parts of admixture, 2-3 parts of cement active modifier, 2-3 parts of auxiliary agent, and the water-solid ratio is 0.4; The cement active modifier comprises component A and component B; The component A is an active agent that is surface-inertly modified by a passivation layer, wherein the passivation layer comprises ethylene-tetrafluoroethylene copolymer, silk fibroin modified fiber, silane coupling agent, and glycidyl methacrylate graft-modified soybean protein adhesive; The mass ratio of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber is 4:3, the addition amount of glycidyl methacrylate grafted modified soybean protein adhesive is 10% of the sum of the mass of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber, and the addition amount of silane coupling agent is 3% of the sum of the mass of ethylene-tetrafluoroethylene copolymer and silk fibroin modified fiber; The component B is a decomposition liquid of the passivation layer in the component A, and the component B includes papain and neutral protease; The active agent in component A comprises the following components in parts by weight: 5 parts of redispersible latex powder, 4 parts of lanthanum cerium oxide, 2 parts of starch ether, and 2 parts of low-viscosity cellulose ether; The mass ratio of papain to neutral protease in component B is 0.5-0.75; The added amount of component B is 0.5%-0.6% of the total mass of component A.
2. The rare earth-containing modified sulphoaluminate cement protective material according to claim 1, characterized in that: The admixture includes the following components in parts by weight: 12 parts of 200-mesh refined iron powder, 6 parts of 150-mesh magnetite, 3 parts of 1250-mesh microsilica powder, and 10 parts of fly ash.
3. The rare earth-containing modified sulphoaluminate cement protective material according to claim 1, characterized in that: The additives include the following components: a water reducer and a defoamer. The amount of the water reducer is 1-1.2% of the mass of the composite sulphoaluminate cement, and the amount of the defoamer is 0.4-0.5% of the mass of the composite sulphoaluminate cement. The water reducer is a polycarboxylate water reducer, and the defoamer is an organosilicon defoamer.
4. The rare earth-containing modified sulphoaluminate cement protective material according to claim 1, characterized in that: The silk fibroin modified fiber is prepared by the following method: putting tussah silkworm cocoons into a sodium carbonate solution with a mass percentage of 0.5% at a bath ratio of 1:50, placing the solution in a constant temperature water bath and boiling for 30 minutes, then taking it out, putting the tussah silkworm cocoons into a sodium carbonate solution with a mass percentage of 0.5% at a bath ratio of 1:50 again, and boiling it in a water bath for 30 minutes, repeating the boiling for 3 times, taking out the boiled tussah silkworm cocoons, drying them in an oven at a temperature of 60° C. to constant weight, cutting the tussah silkworm cocoons into pieces with scissors, putting them into a 9 mol / L ammonium thiocyanate solution at a bath ratio of 1:35, dissolving and filtering, and then dialysis filtering in circulating deionized water for 48 hours, and concentrating the silk fibroin solution obtained by dialysis filtering to a mass percentage of 6%; According to the bath ratio of 1:20, the viscose fiber was put into a 6% silk fibroin solution by mass, and the solution was placed in a constant temperature water bath at a temperature of 55°C. Under the stirring action of an electric stirrer, the solution was taken out after grafting for 45 minutes, placed in an oven at a temperature of 60°C and dried to constant weight, and then repeatedly washed with deionized water. The washed silk fibroin modified viscose fiber was placed in an oven at a temperature of 60°C and dried to constant weight to obtain silk fibroin modified fiber.
5. The rare earth-containing modified sulphoaluminate cement protective material according to claim 1, characterized in that: The glycidyl methacrylate grafted modified soybean protein adhesive is prepared by the following method: adding soybean protein and urea solution into a reaction container, pre-treating in an oil bath at 50° C. for 30 minutes, adding ammonium persulfate and sodium bisulfite initiators into the reaction container, adding glycidyl methacrylate during the reaction for 10 minutes, heating to 70° C., continuing the reaction for 3 hours and then stopping the reaction to obtain the glycidyl methacrylate grafted modified soybean protein adhesive; Among them, the mass ratio of soy protein to glycidyl methacrylate is 4:3.
4.
6. The rare earth-containing modified sulphoaluminate cement protective material according to claim 1, characterized in that: The composite sulphoaluminate cement comprises 42.5 sulphoaluminate cement and 42.5 silicate cement in a mass ratio of 3:
1.
7. A method for preparing a rare earth-containing modified sulphoaluminate cement protective material according to any one of claims 1 to 6, characterized in that: The steps include: S1. Prepare component A: select redispersible latex powder, lanthanum cerium oxide, starch ether, and low-viscosity cellulose ether as raw materials for the active agent, and compress and granulate the redispersible latex powder, lanthanum cerium oxide, starch ether, and low-viscosity cellulose ether in a dry granulator to obtain active agent particles for standby use; Adding silk fibroin modified fiber, silane coupling agent, and glycidyl methacrylate grafted modified soybean protein adhesive into the melt of ethylene-tetrafluoroethylene copolymer, stirring at a constant temperature of 50° C. for 2-3 hours, to obtain a passivating agent; The passivating agent is uniformly sprayed on the active agent particles, and after drying, the active agent with surface inertness modified by the passivating layer is obtained, wherein the active agent with surface inertness modified by the passivating layer is component A; Preparation of component B: using papain and neutral protease as raw materials to prepare enzymatic hydrolysis solution, component B is used together with component A; S2. According to the water-to-solid ratio of 0.4, the composite sulphoaluminate cement, admixture, component A, component B and additives are placed in a mixing tank containing water, stirred at a speed of 300 rpm for 3 minutes, allowed to stand for 1 minute for maturation, and stirred for another minute to obtain the sulphoaluminate cement protective material.
Citation Information
Patent Citations
Impermeable sprayed concrete
CN113321474A